Quantum field theory : a quantum computation approach - Meurice, Yannick (IOP (Series). Release 21., 2021)
This book introduces quantum field theory models from a classical point of view. Practical applications are discussed, along with recent progress for quantum computations and quantum simulations experiments. New developments concerning discrete aspects of continuous symmetries and topological solutions in tensorial formulations of gauge theories are also reported. Quantum Field Theory: A Quantum Computation Approach requires no prior knowledge beyond undergraduate quantum mechanics and classical electrodynamics. With exercises involving Mathematica and Python with solutions provided, the book is an ideal guide for graduate students and researchers in high-energy, condensed matter and atomic physics.